2020
DOI: 10.1016/j.heliyon.2020.e05716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health and environmental risks for juvenile tilapia (Oreochromis niloticus) exposed to florfenicol

Abstract: Intensive fish cultivation has a high incidence of infection, which is often controlled by administering antibiotics. Florfenicol (FF) is one of the two antimicrobial drugs permitted for aquaculture in Brazil. Due to their intensive use, potentially harmful effects on aquatic organisms are of great concern. In this sense, we investigated whether the presence of FF in cultivation water could change the health parameters of Nile tilapia. For this, we evaluated hemoglobin, hematocrit, mean corpuscular hemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The inability to produce an antioxidant defence system leads to the expression of oxidative stress [ 5 ]. The earlier studies asserted the ability of FFC to inflict oxidative stress on O. niloticus juveniles [ 5 , 11 ]. Oxidative stress participates in the liver fibrogenic response and often results in fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inability to produce an antioxidant defence system leads to the expression of oxidative stress [ 5 ]. The earlier studies asserted the ability of FFC to inflict oxidative stress on O. niloticus juveniles [ 5 , 11 ]. Oxidative stress participates in the liver fibrogenic response and often results in fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney has a high capacity for the uptake of lipid-binding proteins and lipid-regulating hormones [ 32 ], and peroxidation of lipids persists in the kidney tissues. As renal injury upon oxidative stress has been documented in several animals [ 5 , 32 ], the documentation of glomerulopathy and degeneration of renal tubules upon dietary FFC administration in O. niloticus was considered befitting. The observations on the increase in MDA levels and decreased GST activity due to the drug sulfasalazine in rat liver and kidney tissues were concomitant with the present study, implying considerable hepatic and renal toxicity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study has proven that florfenicol has a suppressive effect on humoral and cellular immune responses and lymphoid organ destruction and haematopoietic tissue IgM immunoreactive cells (Lunden et al, 1999; Reda et al, 2013). Furthermore, Shiroma et al (2020) have found that florfenicol causes lipid peroxidation and DNA damage because of antioxidant depletion and increased reactive oxygen species (ROS) accumulation even at low concentrations, posing health risks to exposed tilapia. High levels of ROS can harm the immune system by disrupting the periphery immune system and activating leukocytes (Tavassolifar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%